The four-winged dinosaur [videorecording (DVD)] - Davis, Mark; Lewman, Lance (WGBH Boston Video, 2008)
In 2002, the discovery of a beautiful and bizarre fossil astonished scientists and reignited the debate over the origin of flight. With four wings and superbly preserved feathers, the 130 million-year-old creature was like nothing paleontologists had ever seen before. In this program, Nova travels to the Chinese stone quarry where the fossil was discovered - a famed fossil treasure-trove - and teams up with the world's leading figures in paleontology, biomechanics, aerodynamics, animation, and scientific reconstruction to perform an unorthodox experiment: a wind tunnel flight test of a scientific replica of the ancient oddity. Dubbed Microraptor, the crow-sized fossil is one of the smallest dinosaurs ever found and one of the most controversial, challenging conventional theories and assumptions about the evolution of flight.